Evaluation of the stability enhancement of the conventional sliding mode controller using whale optimization algorithm - Aws Mahmood Abdullah; Ali Mohsin Kaittan; Mustafa Sabah Taha (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
The proposed work is an attempt to investigate the stability of the nonlinear system by using a whale optimization algorithm as of one of the meta-heuristic optimization methods, and this investigation was conducted on a single inverted pendulum as a study model. The evaluation measures which were used in this article values of gain and sliding surface of the conventional sliding mode controller to illustrate the extent of the system`s stability. Furthermore, control action, the relationship between error and its derivative, desired, and actual position in addition to sliding response graphically showed the feasibility of the proposed solution. The attained results illustrated considerable improvement in the settling time and minimizing the impact of chattering behavior.